The use of carboxylesterases as biomarkers of pesticide exposure in bivalves: a methodological approach - Solé, Montserrat (2020)
Bivalves are worldwide sentinels of anthropogenic pollution. The inclusion of biomarker responses in chemical monitoring is a recommended practise that has to overcome some diﬃculties. One of them is the time frame between sample collection and sample processing in order to ensure the preservation of enzymatic activities. In the presentstudy, threebivalve species ofcommercial interest (mussel, Mytilus galloprovincialis, razor shell, Solen marginatus, and cockle, Cerastoderma edule) were processed within<2h after being retrieved from their natural habitat, and 24h after being transported in air under cold conditions (6–8°C) to laboratory facilities. The enzymatic activities were compared in the three species submitted to both conditions revealing no diﬀerences in terms of carboxylesterase dependent activities (CEs) using diﬀerent substrates: p-nitrophenyl acetate (pNPA), pnitrophenyl butyrate (pNPB), 1-naphthyl acetate (1-NA), 1-naphthyl butyrate (1-NB) and 2-naphthyl acetate (2NA). In mussels, three tissues were selected (haemolymph, gills and digestive gland). For comparative purposes, in razor shell and cockle only digestive gland was considered as it is the main metabolic organ. Baseline enzymatic activities forCEs werecharacterised inthedigestive gland ofthethreebivalves using four outofthe ﬁve selected CE substrates as well as the kinetic parameters (Vmax and Km) and catalytic eﬃciency. The in vitro sensitivity to the organophosphorus metabolite chlorpyrifos oxon was also calculated. IC50 values (pM-nM range) were lower than those obtained for vertebrate groups which suggest that bivalves have high protection eﬃciency against this pesticide as well as species dependent particularities.